2006
DOI: 10.1111/j.1365-246x.2006.02935.x
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional resonances in Alpine valleys identified from ambient vibration wavefields

Abstract: International audienceAlthough numerical simulations have for long shown the importance of 2-D resonances in site effect estimations of sediment-filled valleys, this phenomenon is usually not taken into account by current hazard assessment techniques. We present an approach to identify the resonance behaviour of a typical Alpine valley by analysis of ambient noise recorded simultaneously on a dense array. The applicability of the method is evaluated further using synthetic ambient noise acquired with current 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 26 publications
9
82
0
1
Order By: Relevance
“…Similar to what is observed across sediment-filled valleys in numerical simulations (e.g., Bouchon 1985, Frischknecht andWagner 2004) and in real data (e.g., Tucker and King 1984, Roten et al 2006), we expect the resonance frequency for such a normal mode resonance to be approximately equal over the entire extent of the landslide body, regardless of its thickness at each site, alike Burjanek et al (2012). Using classical 1D transfer function theory and the obtained velocity model (e.g., for S13 and S20, see Figure 6) one might pre-estimate that a thickness of the lowvelocity body of around 30 to 35 m will correspond to a fundamental frequency of around 2.5 Hz.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar to what is observed across sediment-filled valleys in numerical simulations (e.g., Bouchon 1985, Frischknecht andWagner 2004) and in real data (e.g., Tucker and King 1984, Roten et al 2006), we expect the resonance frequency for such a normal mode resonance to be approximately equal over the entire extent of the landslide body, regardless of its thickness at each site, alike Burjanek et al (2012). Using classical 1D transfer function theory and the obtained velocity model (e.g., for S13 and S20, see Figure 6) one might pre-estimate that a thickness of the lowvelocity body of around 30 to 35 m will correspond to a fundamental frequency of around 2.5 Hz.…”
Section: Discussionsupporting
confidence: 64%
“…Such peaks are found from almost all stations on the landslide body as well as outside of it. Although one might expect a distinct vertical component for the SV modes other studies describing similar directional low-frequency amplification in river valleys (e.g., Steimen et al 2003, Roten et al 2006 indicate that peaks of the fundamental mode of SV resonance might not be visible in the vertical component. Due to the apparent heterogeneous structure in elongated sediment-filled river valleys, these patterns cannot be created by horizontally propagating surface waves and cannot be interpreted classically in terms of 1D resonance, but may be explained with a wave front propagating almost vertically at a slight angle.…”
Section: Horizontal-to-vertical Spectral Ratios and Directivity Analymentioning
confidence: 94%
“…Moreover, the simple relation linking fundamental frequency, shear-wave velocity and depth is valid according to a 1-D model assumption that is not the geometry of most valleys. For example, while BARD and BOUCHON (1985) discussed the 2-D model shapes of a theoretical valley, STEIMEN et al (2003) and ROTEN et al (2004) recently showed experimentally the strong 2-D effect of valley shape on the resonance frequency deduced from ambient seismic noise.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the simple relation linking fundamental frequency, shear wave velocity and depth is valid for a 1D model, which is not the geometry of most valleys. For instance, Steimen et al [2003] and Roten et al [2004] recently showed experimentally the strong 2D effect of valley shape on the resonance frequency deduced from ambient seismic noise. However, according to the concept of critical shape ratio proposed by Bard and Bouchon [1985], who numerically studied the dynamic response of various 2D structures shapes, the seismic behaviour of both landslides should be mainly characterized by one-dimensional resonance and surface wave propagation.…”
Section: Seismic Noise Theorymentioning
confidence: 99%